2003
DOI: 10.2190/ut6d-rdfg-lbt7-g39n
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Mood and Anxiety Syndromes in Primary Care: Who Gets Identified?

Abstract: Neither screening for nor diagnosis of mood and anxiety syndromes is a routine part of primary care of children and adolescents. Efforts to improve care must include practical, validated screening procedures to enhance assessment for mood and anxiety syndromes, particularly among children in whom primary care clinicians identify psychosocial problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 32 publications
1
46
0
2
Order By: Relevance
“…Clearly, there is room for CHPs to improve their screening performance. Although there are several screening instruments for identifying psychosocial problems, identification of psychosocial problems remains inaccurate [14][15][16][17][18]. One reason for this is that physicians use these tools infrequently when screening psychosocial www.elsevier.com/locate/pateducou Patient Education and Counseling 60 (2006) [57][58][59][60][61][62][63][64][65] problems in children [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is room for CHPs to improve their screening performance. Although there are several screening instruments for identifying psychosocial problems, identification of psychosocial problems remains inaccurate [14][15][16][17][18]. One reason for this is that physicians use these tools infrequently when screening psychosocial www.elsevier.com/locate/pateducou Patient Education and Counseling 60 (2006) [57][58][59][60][61][62][63][64][65] problems in children [19].…”
Section: Introductionmentioning
confidence: 99%
“…22 The briefer version of the PSC 3 is broadly used, with >40 published studies. 23 These studies have shown that the PSC-17 yields higher detection rates than pediatricians relying on clinical judgment alone 24 and has risk rates comparable to those of the PSC-35, 3 semistructured interviews (Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version), 25 and longer questionnaire measures. 2 The PSC-17 was derived from the PSC-35 through an exploratory factor analysis conducted on data collected from the 1994 to 1999 Child Behavior Study (CBS), a nationally representative sample of >20 000 pediatric outpatients.…”
mentioning
confidence: 99%
“…10,11 Furthermore, physicians can fail to recognize pediatric anxiety in children who do present for care, and even when anxiety is recognized, it is frequently treated sub-optimally. 9,12,13 The objective of this review was to describe the epidemiology, etiology, pathophysiology, diagnosis, and treatment of pediatric anxiety disorders. Given the fact that anxiety disorders more often co-occur and given the amount of similarities among these syndromes, this paper broadly discusses ideas that are relevant to anxiety disorders as a group.…”
Section: Introductionmentioning
confidence: 99%